Differential expression and prognostic value of long non‐coding RNA in HPV‐negative head and neck squamous cell carcinoma. Issue 7 (25th March 2018) - Haque, Sulsal‐Ul; Niu, Liang; Kuhnell, Damaris; Hendershot, Jacob; Biesiada, Jacek; Niu, Wen; Hagan, Matthew C.; Kelsey, Karl T.; Casper, Keith A.; Wise‐Draper, Trisha M.; Medvedovic, Mario; Langevin, Scott M.
Abstract: Background: Long non‐coding RNA (lncRNA) has emerged as a new avenue of interest due to its various biological functions in cancer. Abnormal expression of lncRNA has been reported in other malignancies but has been understudied in head and neck squamous cell carcinoma (HNSCC). Methods: The lncRNA expression was interrogated via quantitative real‐time polymerase chain reaction (qRT‐PCR) array for 19 human papillomavirus (HPV)‐negative HNSCC tumor‐normal pairs. The Cancer Genome Atlas (TCGA) was used to validate these results. The association between differentially expressed lncRNA and survival outcomes was analyzed. Results: Differential expression was validated for 5 lncRNA ( SPRY4‐IT1, HEIH, LUCAT1, LINC00152, and HAND2‐AS1 ). There was also an inverse association between MEG3 expression (not significantly differentially expressed in TCGA tumors but highly variable expression) and 3‐year recurrence‐free survival (RFS). Conclusion: We identified and validated differential expression of 5 lncRNA in HPV‐negative HNSCC. Low MEG3 expression was associated with favorable 3‐year RFS, although the significance of this finding remains unclear.